Adverse childhood experience referring to parental relationship is associated with the risk of alcohol dependence and with COMT Val158Met polymorphism, but out of gene-environment interactions. (1st June 2022) - Merkulova, T.; Chuprova, N.; Solovieva, M.; Nikolishin, A.; Kibitov, A.; Grechany, S.; Baranok, N.; Rybakova, K.; Soldatkin, V.; Yakovlev, A.; Trusova, A.; Ponizovsky, P.; et al.
Abstract : Introduction: Gene-environment interactions (GxE) are considered to make a substantial impact on the risk of alcohol dependence (AD). Objectives: The aim of the study: to test the associations between the functional polymorphism Val158Met (rs6265) in the catechol-O-methyl transferase (COMT) gene, affecting dopamine neurotransmission, and adverse childhood experiences (ACE) and their GxE interactions with AD risk. Methods: The study included 149 AD inpatients (mean age 29.9 (SD=3.91), 16.1% females) and 201 healthy volunteers (23.3 (2.48), 30.1% females). The Adverse Childhood Experiences International Questionnaire (ACE-IQ) was used for assessing ACE. COMT Val158Met polymorphism was detected by RT-PCR. Results: First, COMT Val158Met polymorphism was associated only with adverse childhood experience referring o parental relationship (ACE-IQ), but differently in two groups. Healthy minor Met158 carriers have lower scores on the subscale "relationship with parents/guardians" (P) (p=0.025) and "physical neglect" (PN) (p=0.059) vs. homozygous Val158 carriers. However, AD patients - Met158carriers have a tendency to a higher score on the subscale "one or no parents, parental separation or divorce" (PSD) (p=0.078). Then logistic regression revealed associations of these ACE scores with increased AD risk: P (p=0.001, OR=1.186, 95%CI [1.069-1.315]), PN (p=0.024, OR=1.254, 95%CI [1.030-1.526]), and PSD (p=0.016, OR=1.499, 95%CI [1.080-2.082]). No associations of COMT Val158Met alone or in interactions with these ACE-IQ scores with the AD risk were found. Conclusions: Adverse childhood experience referring to parental relationship is associated with alcohol dependence risk and separately with COMT Val158Met, but no clear interactions in frame of GxE has been supported. Disclosure: No significant relationships.